ANALISIS PENGARUH FAKTOR KUNJUNGAN BALITA KE POSYANDU DESA JENGGOT - Fatmawati, Istiadah; Shanti Astuti, Arlia; Soraya Niah, Najah (LPPM STIKES HUSADA JOMBANG, 2024)
In the form of Community Resource Health Efforts (UKBM), Posyandu is a place that is managed and organized with the community in its implementation in health development. Based on data from preliminary studies at the Posyandu, Beard Village received as many as 52.5% of toddlers who came. The purpose of this study was to analyze the factors that influence toddler visits to posyandu. The research method in this study is correlation analytic using a Cross Sectional approach. The independent variable is motivation and family support, while the dependent variable is toddler visits. The population was 78 respondents, the sample size was 65 respondents. Sampling using Simple Random Sampling. The instruments used are questionnaires and KMS. Statistical test using Regust Ordinal with a meaning value of α 0.05. The results of the Regust Ordinal satistic test for the relationship between family motivation and toddler visits to posyandu obtained ρ values of 0.001 < α 0.05 which showed a motivational relationship with toddler visits at posyandu cempaka, while the results of the Regust Ordinal statistical test for family support with toddler visits obtained ρ values of 0.001 < α 0.05 which showed a relationship between family support and toddler visits at the Beard Village posyandu. It is hoped that families will be more active in providing support to mothers to bring their babies to posyandu. Because family support is needed in providing support or advice.